Combining DOE With Neurofuzzy Logic for Healthy Mineral Nutrition of Pistachio Rootstocks in vitro Culture - Nezami-Alanagh, Esmaeil; Garoosi, Ghasem-Ali; Landín, Mariana; Gallego, Pedro Pablo (Frontiers in Plant Science, 2018)
The aim of this study was to determine the effects of Murashige and Skoog (MS) salts on optimal growth of two pistachio rootstocks, P. vera cv. ‘Ghazvini’ and ‘UCB1’ using design of experiments (DOE) and artificial intelligence (AI) tools. MS medium with 14 macro- and micro-elements was used as base point and its concentration varied from 0 to 5× MS concentrations. Design of experiments (DOE) software was used to generate a five-dimensional design space by categorizing MS salts into five independent factors (NH4NO3, KNO3, mesos, micros and iron), reducing the experimental design space from 3,125 to just 29 treatments. Typical plant growth parameters such as shoot quality (SQ), proliferation rate (PR), shoot length (SL), and some physiological disorders including shoot-tip necrosis (STN) and callus formation at the base of explants (BC) were evaluated for each treatment. The results were successfully modeled using neurofuzzy logic software. The model delivered new insights, by different sets of ‘IF–THEN’ rules, pinpointing the key role of some ion interactions (SO42- × Cl-, K+ × SO42- × EDTA- and Fe2+ × Cu2+ × NO3-) for SQ, PR and SL, whilst physiological disorders (STN and BC) were governed mainly by independent ions as Fe2+ and EDTA-, respectively. In our opinion, the methodology and results obtained in this study is extremely useful to understand the effect of mineral nutrients on pistachio in vitro culture, through discovering new complex interactions among macro- and micro-elements which can be implemented to design new media of plant tissue culture and improve healthy plant micropropagation for any plant species